Protozoan impact on bacterial biofilm formation - Rychert, Krzysztof; Neu, Thomas (Biological Letters, 2011)
Confocal laser scanning microscopy in combination with digital image analysis was used to assess the impact of protozoa on bacterial colonisation of surfaces. Bacterial biofilms were developed from activated sludge in microscope flow cells and were exposed to the grazing pressure of protozoa. The protozoan community from healthy activated sludge and a culture of flagellate Bodo saltans were used as grazers. Experiments comprised 48-h incubations in 3 treatment variants: bacteria with protozoa, bacteria with protozoa added after some time and bacteria without protozoa. When necessary, the elimination of protozoa from the inoculum was carried out with cycloheximide and NiSO4. Experiments demonstrated that protozoa from healthy activated sludge initially disturbed the biofilm development but later they could stimulate its growth. Similar results could be established in the experiment with Bodo saltans (inoculum: 1000 cells/ml), however differences were not statistically significant. The finding that protozoa support biofilm development during specific stages may be relevant for biofilm studies with mixed environmental biofilm communities.